Effect of Blanching on Enzyme Activity and Bioactive Compounds of Blackberry - Noreña,Caciano Zapata (2018)
ABSTRACT The inactivation of peroxidase and polyphenol oxidase and the degradation of phenolic compounds, anthocyanins, and antioxidant activity in blackberry were investigated during blanching in water at 80-90 °C, and in steam, from 0 to 10 minutes. The enzyme kinetics indicated the presence of two isoenzymes with different thermal stability, following two-phase model, in which the reaction rate constant increased with increasing temperature for both the heat labile and heat resistant component. The phenolic compounds also followed a biphasic pattern, indicating a more heat resistant fraction, and the rate constants increased with increasing temperature. For the antioxidant activity and anthocyanins, the first order kinetic model (R2>0.982) indicated an increase in degradation rate constants with temperature, from 0.050 to 0.137min-1 for DPPH, 0.085 to 0.285min-1 for ABTS, and 0.017 to 0.052 min-1 for anthocyanins.